Optimization and Management of Quality of Life in the Region, Using the Example of the Primorye Territory (Russia) - MARTYSHENKO, Natalya Stepanovna (Journal of Advanced Research in Law and Economics, 2017)
The issue of improving the quality of life in the Russian regions is one of the major issues of all levels of governing bodies. The basic idea of the proposed management optimization model of quality of life of the region considers a synergistic effect of changes of various quality of life indicators. The main difficulty of managing the synergistic effect in social and economic systems is that, unlike physical systems, which adopt appropriate units of measurement and quantitative evaluation methods for management indicators, at this stage of the theory development, for such systems objective evaluation methods for the synergy level do not exist. The present optimization mathematical model allows us to evaluate the effectiveness of the regional budget distribution in terms of improving the region population quality of life. The paper discusses methodological approaches of evaluating the model parameters. With reference to questionnaires of the Primorye Territory population, the evaluation distribution was defined for factors, which affect the quality of life for the time periods. The paper presents the methodical approaches to the synergy evaluation of the quality of life (QOL) indicators. The considered optimization model is based on the generalized indicators of the QOL. The proposed model allows us to structure and synthesize the views of experts in various fields of economy. Using the model, the structure of the funds distribution, which was accepted to be performed, can be estimated for the region in the near future.